Challenges in changing to non-chlorofluorocarbon inhalers in the treatment of asthma. Issue 890 (1st December 1999) - Walley, T; Bundred, P; Rannard, A; Bogg, J
Abstract : The chlorofluorocarbon (CFC)-based metered dose inhaler, which has been the mainstay of the management of obstructive lung diseases, will soon be phased out world wide and replaced by CFC-free devices. Patients will have to be changed to the devices in a co-ordinated manner to avoid any risk to their health and safety. The different shapes and aerosol delivery characteristics of the new inhalers, as well as their distinctive taste, could add to the levels of poor drug use already experienced in asthma. From previous change scenarios in disease management, the potential for unstable asthma control is a real possibility with all the attendant costs. By using the time available before CFC-based inhalers are withdrawn, there is an opportunity to enhance asthma management during this period of change.